Restructuring Sibolga Beach as an Effort to Increase Tourism Competitiveness and the Local Economy - Sirait, Jumaria; Manalu, Monika; Simanullang, Yohanna; Simanjuntak, Clara (Jujurnal Publisher, 2025)
This study aims to analyze and formulate a model for the restructuring of the coastal areas in Sibolga City as a comprehensive strategy to enhance the competitiveness of the tourism sector and drive sustainable local economic growth. Although Sibolga has significant marine tourism potential, inadequate infrastructure, suboptimal spatial planning, and limited tourism product innovation often hinder tourist visits and their economic impact on the community. The research method used is descriptive qualitative with a case study approach, involving the analysis of secondary data (regional regulations, tourism master plans) and primary data collection through in-depth interviews with stakeholders (local government, business operators, and local communities). The results show that the restructuring of the coastal area requires not only physical improvements (reorganization of facilities, infrastructure, and cleanliness) but also managerial and institutional restructuring. The proposed restructuring model includes three main pillars: 1) Improving the quality and quantity of infrastructure that meets national standards and is environmentally friendly; 2) Developing thematic tourism products integrated with local culture and maritime potential; and 3) Strengthening institutional capacity and community participation in the management and tourism value chain. The implementation of this restructuring is expected to increase tourist visits, extend the length of stay, create new business opportunities, and directly improve the income and economic well-being of the Sibolga community, making it a leading tourist destination on the western coast of North Sumatra.